Associations of sleep duration and sleep–wake rhythm with lung parenchymal abnormalities on computed tomography: The MESA study. (9th September 2021) - Kim, John S.; Dashti, Hassan S.; Huang, Tianyi; Cade, Brian E.; Podolanczuk, Anna J.; O'Hearn, Daniel J.; Hoffman, Eric A.; Wang, Heming; Blaikley, John; Barr, R. Graham; Redline, Susan
Abstract: Impairment of the circadian rhythm promotes lung inflammation and fibrosis in pre‐clinical models. We aimed to examine whether short and/or long sleep duration and other markers of sleep–wake patterns are associated with a greater burden of lung parenchymal abnormalities on computed tomography among adults. We cross‐sectionally examined associations of sleep duration captured by actigraphy with interstitial lung abnormalities ( n = 1111) and high attenuation areas ( n = 1416) on computed tomography scan in the Multi‐Ethnic Study of Atherosclerosis at Exam 5 (2010–2013). We adjusted for potential confounders in logistic and linear regression models for interstitial lung abnormalities and high attenuation area, respectively. High attenuation area models were also adjusted for study site, lung volume imaged, radiation dose and stratified by body mass index. Secondary exposures were self‐reported sleep duration, sleep fragmentation index, sleep midpoint and chronotype. The mean age of those with longer sleep duration (≥ 8 hr) was 70 years and the prevalence of interstitial lung abnormalities was 14%. Increasing actigraphy‐based sleep duration among participants with ≥ 8 hr of sleep was associated with a higher adjusted odds of interstitial lung abnormalities (odds ratio of 2.66 per 1‐hr increment, 95% confidence interval 1.42–4.99). Longer sleep duration and higher sleep fragmentation index were associated with greater high attenuation area on computed tomography among participants with a body mass index < 25 kg m −2 ( p ‐value for interaction < 0.02). Self‐reported sleep duration, later sleep midpoint and evening chronotype were not associated with outcomes. Actigraphy‐based longer sleep duration and sleep fragmentation were associated with a greater burden of lung abnormalities on computed tomography scan.